2014
DOI: 10.3389/fnbeh.2014.00257
|View full text |Cite
|
Sign up to set email alerts
|

Mixed housing with DBA/2 mice induces stress in C57BL/6 mice: implications for interventions based on social enrichment

Abstract: Several behavioral interventions, based on social enrichment and observational learning are applied in treatment of neuropsychiatric disorders. However, the mechanism of such modulatory effect and the safety of applied methods on individuals involved in social support need further investigation. We took advantage of known differences between inbred mouse strains to reveal the effect of social enrichment on behavior and neurobiology of animals with different behavioral phenotypes. C57BL/6 and DBA/2 female mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 94 publications
2
21
0
Order By: Relevance
“…There are well known differences in immune and physiological processes between C57Bl/6J and Balb/cJ mice, including stress that is well known to modulate gastric emptying . Blood corticosterone levels were tested as a quantitative measure of stress from three groups of mice: baseline C57Bl/6J mice that did not undergo gastric emptying and C57Bl/6J and Balb/cJ mice that underwent gastric emptying.…”
Section: Resultsmentioning
confidence: 99%
“…There are well known differences in immune and physiological processes between C57Bl/6J and Balb/cJ mice, including stress that is well known to modulate gastric emptying . Blood corticosterone levels were tested as a quantitative measure of stress from three groups of mice: baseline C57Bl/6J mice that did not undergo gastric emptying and C57Bl/6J and Balb/cJ mice that underwent gastric emptying.…”
Section: Resultsmentioning
confidence: 99%
“…First, all of our animals were male C57Bl/6 mice. C57Bl/6 mice were chosen for their moderate levels of anxiety-like behavior ((Belzung, 2001, Belzung and Griebel, 2001, Kulesskaya et al, 2014, Kulesskaya and Voikar, 2014) In order to collect more consistent results, no females or other strains were tested in this study. However, future studies should be conducted to observe the behavior of different species or gender of mice with TIC injury since facial neuropathic pain in humans occurs preferentially in females (Rauhala et al, 2000, Macfarlane et al, 2001, Macfarlane et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well known that different inbred mouse strains show different emotional responses to social stress, and such differences have been attributed to genetic differences of the strains . We previously surveyed multiple inbred mouse strains and found that the vicarious freezing response was highly variable among different strains.…”
Section: Main Bodymentioning
confidence: 98%